The influence of emotional intelligence on employees’ performance in Johor Petroleum Development Corporation Berhad / Nor Azieyati A’yudin - A’yudin, Nor Azieyati (Faculty of Business and Management, 2018)
The purpose of this study was to analyze the influence of emotional intelligence (EI) on employees’ performance in Johor Petroleum Development Corporation Berhad. The factors that affect employees’ performance are self-awareness, self-management and relationship management. Furthermore, this research was guided by four research objectives which the researcher needs to answer. The research is quantitative research which the researcher used self-administered questionnaires as instrument to collect data. The data had been collected from 93% of 86 respondents which withdrawn from a total of 110 elements of population by using convenience sampling method. The data are coded using Statistical Package for Social Science (SPSS) version 22.0 after collecting information from the respondents. The study recommended that Johor Petroleum Development Corporation Berhad need to focus on self-management because it gives the biggest impact towards employees’ performance. As well as the organization need to focus on self-management and self-awareness as it can lead to the positive behaviors toward work environment which then achieve the organizational goals and objectives.